Evidence about the transmission of monetary policy - Olli-Matti Laine (Bank of Finland, 2022)
This doctoral dissertation analyses the transmission of monetary policy. It applies a variety of empirical methods to study how conventional and unconventional monetary policy measures transmit to different macroeconomic and financial variables. The first article analyses the effect of monetary policy on the term structure of stock market risk premia. The implied term structure is solved in a novel way utilizing equity analysts' dividend forecasts and dividend future prices. The results show that monetary policy affects risk premia differently at different discounting horizons. Monetary policy easing lowers the short-horizon premia and raises the long-horizon premia. The effect on the average risk premium is positive. The second article studies the effect of targeted longer-term refinancing operations on bank lending. The results suggest that these targeted operations stimulated bank lending to firms. However, no evidence about a positive effect on lending to households is found. The third article examines the effects of conventional monetary policy during the 2008 financial crisis and the era of ultra-low interest rates. Several earlier studies conclude that the effects of conventional monetary policy shocks stayed almost the same during and after the financial crisis. Revisiting this research question, the findings suggest that the impulse response functions of industrial production and unemployment changed drastically after the financial crisis.
urn:nbn:fi:bof-202206031258
Keywords: E44; E51; E52; E58; E6; G12; G21; 330; monetary policy; stock market; bank lending; time-varying effects